PENGARUH MOTIVASI KERJA, DAN KOMPENSASI TERHADAP KINERJA KARYAWAN RUMAH SAKIT DR. MOEWARDI SURAKARTA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MODERATING - galih wisnu wardhana (Optimum: Jurnal Ekonomi dan Pembangunan, 2018)
The purpose of this study is to analyze and provide evidence empirically that the motivation of work, compensation, job satisfaction affect the performance of employees Dr. Moewardi Surakarta Hospital. The population in this study are employees Dr. Moewardi Surakarta Hospital. The results of this study proves the regression results on the regression equation that Motivation has a significant influence on the performance of employees Dr.Moewardi Surakarta. Compensation has a significant influence on the performance of employees and lecturers. Satisfaction has an insignificant effect on employee and lecturer performance. Satisfaction can strengthen the influence of motivation and compensation to employees and lecturers so that motivation can be summed up as a moderating variable. F test results show that there is no significant effect simultaneously between independent variables consisting of: motivation, compensation and satisfaction to the performance of employees and lecturers . The result of test of R2 (coefficient of determination) is known that variability of dependent variable which can be explained by variability of independent variable equal to 19% while the rest (81%) is explained by other variable not included in regression model like education level, discipline, and leadership